2021
DOI: 10.3390/jcm10091944
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation of Right Ventricular (RV) Performance over Time in COVID-19-Associated ARDS—A Prospective Observational Study

Abstract: (1) Background: To evaluate time-dependent right ventricular (RV) performance in patients with COVID-19-associated acute respiratory distress syndrome (ARDS) undergoing intensive care (ICU) treatment. (2) Methods: This prospective observational study included 21 ICU patients with COVID-19-associated ARDS in a university hospital in 2020 (first wave). Patients were evaluated by transthoracic echocardiography at an early (EE) and late (LE) stage of disease. Echocardiographic parameters describing RV size and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…They found that the early parameters were normal however, RV dysfunction and dilatation was present at 2 weeks which correlated with the severity of ARDS. 20 Although a generalization, these 2 studies show that there is late RV dysfunction related to COVID-19, a finding echoed by our study. In other studies however, while the prevalence of RV strain was high in intubated COVID-19 patients, the RV strain did not indicate the severity of COVID-19…”
Section: Resultssupporting
confidence: 64%
“…They found that the early parameters were normal however, RV dysfunction and dilatation was present at 2 weeks which correlated with the severity of ARDS. 20 Although a generalization, these 2 studies show that there is late RV dysfunction related to COVID-19, a finding echoed by our study. In other studies however, while the prevalence of RV strain was high in intubated COVID-19 patients, the RV strain did not indicate the severity of COVID-19…”
Section: Resultssupporting
confidence: 64%